Transcriptome-guided discovery of novel plant-associated genes in a rhizosphere Pseudomonas - Saati-Santamaría, Zaki; González-Dominici, Lihuén Iraí; Jiménez-Gómez, Alejandro; Morais, Daniel; Tláskal, Vojtěch; Frontela, Irene; Benada, Oldřich; Qi, Li; Sheng, Yang; Rivas, Raúl; Baldrian, Petr; García-Fraile, Paula (Microbiome, 2025)
BACKGROUND: Microorganisms play important ecological roles during interactions with plants, with some strains promoting plant performance. However, the molecular basis of bacterial adaptation to the plant environment remains poorly understood. Microbial plant growth promotion is a complex process that likely involves numerous bacterial genes, many of which remain uncharacterized. In this study, we aimed to identify genes tightly associated with the bacterial adaptation to plant hosts by integrating transcriptomic data from bacteria colonizing roots with comparative genomic and metagenomic analyses. RESULTS: Here, we identified a set of bacterial genes that were significantly upregulated during root colonization and are more abundant in rhizosphere communities than in bulk soils. Many of these genes had not been previously linked to plant-bacteria interactions. Comparative genomic analyses revealed some of these genes as more prevalent in plant-associated Pseudomonas genomes than in genomes from other environments. We argue that these genes may play relevant biological roles in this host, although only a few have been previously associated with plant colonization. Among them, we focused on a gene homologous to yafL, which encodes a cysteine peptidase of the NlpC/P60 family, known for its role in peptidoglycan remodelling. This gene is more abundant in rhizosphere microbiomes than in bulk soils, and it showed induced expression on the root surface, supporting its ecological relevance in root-associated environments. Functional validation using a knockout mutant confirmed its contribution to plant-bacteria interactions by affecting root architecture and plant growth. CONCLUSIONS: This study provides new insights into the genetic basis of bacterial adaptation to the plant root environment. By integrating transcriptomic and comparative genomic analyses, we identified numerous genes upregulated during root colonization that are enriched in plant-associated Pseudomonas genomes. Our findings highlight previously overlooked bacterial functions with potential roles in plant-microbe interactions. The functional validation of a protein of the NlpC/P60 family supports its involvement in plant-bacteria interactions and underscores the importance of uncharacterized genes in shaping beneficial associations in the rhizosphere. Video Abstract.
Keywords: metagenomika; Soil Microbiology; kořeny rostlin; Rhizosphere; Gene Expression Profiling; Plant–microbe interactions; NlpC/P60 family; rhizosféra; půdní mikrobiologie; stanovení celkové genové exprese; Peptidoglycan remodelling; Comparative genomics; Transcriptome; Transcriptomics; Plant Roots; Bacterial Proteins; bakteriální proteiny; Metagenomics; Plant growth promotion; transkriptom; Pseudomonas; Root colonization